DESIGN OF DATA COMMUNICATION SYSTEM BETWEEN PROTOTYPE TANK WITH GROUND STATION USING TELEMETRY - Avando Bastari; Endin Tri Hartanto; Arif Wahyudianto; Bagus Irawan (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
The Indonesian Navy is one of the elements of the Indonesian nation which has the duty to maintain the unity of the Republic of Indonesia). Military weapons systems that have a protective layer and are armed with firearms. This vehicle can be controlled remotely so that it can be used as a vehicle for the land defense that is quite powerful and effective. In realizing a data communication system that is efficient and safe against data breaches, the author tries to raise it into a research theme with the title Research Design of a data communication system between a prototype tank and a ground station use telemetry. In carrying out its function as a means of data transactions between prototype tanks and ground stations that work both ways, telemetry will send data from the prototype tank to the ground station and vice versa telemetry will send data from the ground station to the prototype tank. This is the application of two-way communication. The test results obtained a maximum transmission distance of 60 meters.Keywords : Prototype, Telemetry, Ground station